2022
DOI: 10.3389/fimmu.2022.922000
|View full text |Cite
|
Sign up to set email alerts
|

High-Dimensional Immune Profiling by Mass Cytometry Revealed the Circulating Immune Cell Landscape in Patients With Intracranial Aneurysm

Abstract: BackgroundIncreasing evidence supports a critical role of chronic inflammation in intracranial aneurysm (IA). Understanding how the immunological alterations in IA provides opportunities for targeted treatment. However, there is a lack of comprehensive and detailed characterization of the changes in circulating immune cells in IA.ObjectiveTo perform a comprehensive and detailed characterization of the changes in circulating immune cells in patients with IA.MethodsPeripheral blood mononuclear cell samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Inflammatory processes play a significant role in the development of IA 30,31 . Several research exploring the association between chronic inflammation and IAs suggested that persistent disruption of the peripheral immune environment may induce the formation of IAs through inflammatory cascades 32–35 . In the present, it was observed that PBMCs, as a crucial component of the peripheral immune environment, exhibited metabolic dysregulation associated with numerous diseases.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Inflammatory processes play a significant role in the development of IA 30,31 . Several research exploring the association between chronic inflammation and IAs suggested that persistent disruption of the peripheral immune environment may induce the formation of IAs through inflammatory cascades 32–35 . In the present, it was observed that PBMCs, as a crucial component of the peripheral immune environment, exhibited metabolic dysregulation associated with numerous diseases.…”
Section: Discussionmentioning
confidence: 51%
“…30,31 Several research exploring the association between chronic inflammation and IAs suggested that persistent disruption of the peripheral immune environment may induce the formation of IAs through inflammatory cascades. [32][33][34][35] In the present, it was observed that PBMCs, as a crucial component of the peripheral immune environment, exhibited metabolic dysregulation associated with numerous diseases. In our study, metabolic profiling of PBMCs revealed distinct metabolic characteristics among different subsets.…”
Section: Discussionmentioning
confidence: 72%
“…It is increasingly recognized that intracranial aneurysm is a disease that is driven by chronic inflammation (2,4,7). The SII index is a peripheral blood inflammatory index that is used to evaluate systemic inflammation (10), whereas AWE is regarded as a biomarker of aneurysmal wall inflammation (5).…”
Section: Discussionmentioning
confidence: 99%
“…In a pathological study, it was reported that the status of inflammatory processes in the aneurysmal wall correlates well with aneurysmal wall enhancement (AWE) in highresolution magnetic resonance imaging (HR-MRI) (5). Inflammatory processes in the aneurysmal wall also involve the local activation of the immune system, including neutrophil influx followed by the infiltration of macrophages and other inflammatory cells (6,7). It has been reported that cytokine interleukin-10 and the neutrophil to lymphocyte ratio (NLR) are associated with AWE in HR-MRI (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…NK cell activation may play a significant role in the exacerbation of AS (21), suggesting that the increased cytotoxicity mediated by NK cells may contribute to the development of AS. Moreover, the migration ability of NK cells in the peripheral blood of patients with IA is also enhanced (22). NK cells may aggregate and activate in the aneurysm wall during the pathogenesis, which mediates cytotoxicity to promote disease progression.…”
Section: Discussionmentioning
confidence: 99%